The factors that influencing credit card usage among Islamic banking customer a case study in Temerloh / Noor Hidayah Mat Amin - Mat Amin, Noor Hidayah (Faculty of Business Management, 2017)
Credit card is issued by financial institution to users to enable cardholder to make any payment for goods and service. Credit card have become necessity to the public. The credit card issues by financial institution because to give its holder a soft of loan without collateral to be pledged (Mohamed, et al., 2016). This paper aimed to identify the factors that influencing credit card usage among Islamic banking customer in Temerloh Pahang. There are six factor that influencing credit card usage among Islamic banking customer which are easy access to credit, promotion by credit card provider, low minimum payment requirement, attitude, credit card related knowledge, and lastly service quality. Primary data will be collected through series of questions in a questionnaires. The questionnaires will distribute to the 150 respondents among Islamic banking customer. The target population is Islamic banking customer and sampling technique is convenient sampling. Statistical Package for Social Science (SPSS) use to analyse the data and method for data analysis are frequency analysis, reliability analysis, descriptive analysis, Pearson correlation analysis and regression analysis. The findings shows the aggressive promotion by the credit card provider, attitude towards credit card usage and service quality have a positive and significant relationship on the credit card usage among Islamic banking customer. In Malaysian, a certain parties should take action in solve the problem. For example, the government should tighten the rules and give guideline to the cardholder. Other parties like commercial bank should give advisee and explain more about advantages and disadvantages ušing credit card to the customer before customer apply the credit card. Then customer should control their purchase in item of goods or product.